Critical Evaluation of Ayurvedic Plants for Stimulating Intrinsic Antioxidant Response - Shukla, Sunil D.; Bhatnagar, Maheep; Khurana, Sukant (Frontiers in Neuroscience, 2012)
Oxidative damage caused by free radicals plays an important role in the causation and progression of many diseases, including aging. Free radical damage is countered by many mechanisms, including both active antioxidant enzymatic activity in our body and passive antioxidants. Antioxidant response of our body can accommodate increased oxidative damage in diseased states to a level but beyond that level, additional antioxidants are required to combat the increased stress. Apart from the regular dietary sources of antioxidants, many traditional herbal medicines demonstrate a potential to boost antioxidant activity. Rasayana chikitsa that deals with rejuvenation and revitalization is a branch of the Indian traditional medical system of Ayurveda. We review some select herbs described in Rasayana chikitsa that have been assessed by modern means for stimulating intrinsic antioxidant responses in humans. A critical evaluation of Rasayana chikitsa will likely provide urgently needed, actual stimulants of our physiological antioxidant responses and not just more passive antioxidants to an already large catalogue.